Confronting crime: crime control policy under New Labour - Tonry, Michael H. (Cambridge criminal justice series, 2003)
From Labour's promise to be 'tough on crime, tough on the causes of crime', controlling crime and reforming the criminal justice system has been one of the government's key priorities. This work covers the past record of the Labour government, focusing on effective ways of dealing with crime and offenders